2008
DOI: 10.1590/s0104-56872008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Estimulação elétrica nervosa transcutânea em mulheres disfônicas

Abstract: TEMA: estudos mostram correlação entre disfonia e tensão muscular. OBJETIVO: avaliar a atividade elétrica dos músculos supra-hióideos (SH), esternocleidomastóideo (ECM) e trapézio (T) bilateralmente, a dor e a voz, após aplicação da estimulação elétrica nervosa transcutânea (TENS). MÉTODO: participaram dez mulheres com nódulos ou espessamento mucoso bilateral e fenda à fonação. As voluntárias receberam dez sessões de TENS (200µs e 10Hz) por 30 minutos. A dor foi avaliada pela escala visual analógica, a voz por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
(14 reference statements)
1
17
1
9
Order By: Relevance
“…An investigation with similar results was conducted by Guirro et al (12), where 10 participants with dysphonia performed 10 TENS sessions (200 µs and 10 Hz; 4 electrodes applied in the trapezius and sternocleidomastoid muscles bilaterally), with pain relief through VAS. The TENS decreased the Root Media readings of right and left trapezius, left sternocleidomastoid, and suprahyoid muscles during the production of the/e/vowel and for right and left trapezius as well as right and left sternocleidomastoid during spontaneous speech.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…An investigation with similar results was conducted by Guirro et al (12), where 10 participants with dysphonia performed 10 TENS sessions (200 µs and 10 Hz; 4 electrodes applied in the trapezius and sternocleidomastoid muscles bilaterally), with pain relief through VAS. The TENS decreased the Root Media readings of right and left trapezius, left sternocleidomastoid, and suprahyoid muscles during the production of the/e/vowel and for right and left trapezius as well as right and left sternocleidomastoid during spontaneous speech.…”
Section: Discussionmentioning
confidence: 70%
“…Physiotherapy, which consisted of a systematic approach of manual therapy, education, and therapeutic exercises, had similar results to voice therapy, improving voice handicap index scores (11). Transcutaneous electrical nerve stimulation (TENS) has been shown to promote pain relief in trapezius and sternocleidomastoid muscles, decreased the root media readings in trapezius, sternocleidomastoid, and suprahyoid muscles during the production of the/e/vowel and reduce the level of dysphonia and hoarseness during spontaneous speech in dysphonic participants (12). A manual therapy, usually associated with complementary therapies like osteopathy and chiropractic but also used by physiotherapists, which that has been shown to increase range of motion, reduce muscle tension and pain which suggest that may improve voice quality (13, 14) was spinal manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, there are few publications on the applicability of electrical stimulation in the treatment of dysphonia [14][15][16][17][18][19][20] and studies that were part of this review show applicability in different vocal and with different approaches and that there is little proven scientific evidence on their behalf. However, research on the application of this new feature in the speech therapy clinical practice is recent and some questions deserve to be answered because there is controversy in the literature that may be related to the heterogeneity of the samples studied, since the surveys were conducted with different etiological frames of dysphonia, and various ages, as well as the lack of standardization method, and does not define the follow-up of patients during and after treatment.…”
Section: Electrostimulation In the Treatment Of Dysphonia Effect Of Ementioning
confidence: 99%
“…A survey 17 evaluated the effect of TENS on the pattern of activation of masticatory muscles in 10 dysphonic women with nodules or bilateral mucus thickening, and phonation fissure, justified by the fact that women dysphonic present increased muscle tension in the neck and shoulder girdle. TENS was applied on the upper fibers of the trapezius and sternocleidomastoid bilaterally, seeking muscular balance and relaxation of these muscles.…”
Section: Effect Of the Use Of Tens In Women With Muscle Tension Dysphmentioning
confidence: 99%
“…Therapeutic procedures usually involve voice therapy; however, surgical procedures might be necessary in certain cases. Guirro et al [21] found that transcutaneous electrical nerve stimulation (a subtype of NMES) resulted in a decrease in hoarseness, the level of dysphonia and laryngeal injuries as well as relief of pain in women with nodules or bilateral mucus thickening and phonation fissure.…”
Section: Nmes For Dysphonia and Dyspnoeamentioning
confidence: 99%